PENGARUH PERAN ORANG TUA DALAM PEMEROLEHAN BAHASA PADA ANAK USIA 4-5 TAHUN - Sheva Widianti Putri (Universitas Negeri Makassar)
Effect of Parent’s Role in Language Acquisition in 4-5 Years Children. The purpose of this study is to explain the effect of the role of parents on language acquisition in children aged 4-5 years. This analysis uses descriptive analysis. The research method used is the interview method and note-taking method. Researchers interviewed sources and then transcribed them using the note-taking method. The research sample consisted of two sources, namely (1) Adrian Salafas Putra (4 years 5 months old), and (2) Dimas Mahesa (5 years 3 months old). The results of this study are the first sample, children get Javanese language from their parents who come from Java. The second sample, children obtain language vocabulary such as